Subsynchronous Oscillation Characteristics for Direct Drive Wind Farm Based on Complex Torque Coefficient Method - Wenchao Zhai; Qi Jia; Gangui Yan (CSEE Journal of Power and Energy Systems)
Based on subsynchronous oscillation (SSO) caused by the connection of a direct drive wind farm to a weak alternating current (AC) grid, a complex torque model is proposed. By dividing the wind farm into a direct current capacitor and electrical control part, the analytical expression of damping torque for the electrical control part is deduced and the mechanism of system subsynchronous oscillation is analyzed from the perspective of damping. The system stability is determined based on a damping coefficient less than 0, and the influence laws of grid strength, operating conditions, and control parameters on system damping characteristics are analyzed, based on additional subsynchronous oscillation damping control (SSDC) to suppress SSO. Furthermore, the complex torque model of the parallel access system for multiple sub-wind farms is established, and the dynamic interaction between multiple sub-wind farms is preliminarily explored. The time-domain simulation model is built in EMTDC/PSCAD to verify the correctness of the theoretical analysis.